Proinflammatory state, hepcidin, and anemia in older persons - Ferrucci, Luigi; Semba, Richard D; Guralnik, Jack M; Ershler, William B; Bandinelli, Stefania; Patel, Kushang V; Sun, Kai; Woodman, Richard C; Andrews, Nancy C; Cotter, Robert J; Ganz, Tomas; Nemeth, Elizabeta; et al. (Blood, 2010)
In patients with overt inflammatory diseases, up-regulated hepcidin impairs iron absorption and macrophage release, causing anemia. Whether the mild proinflammatory state of aging is associated with increased hepcidin is unknown. We characterized the relationships between urinary hepcidin, iron status, anemia, and inflammation in 582 patients 65 years or older participating in the InCHIANTI (Invecchiare in Chianti, "Aging in the Chianti Area") study, a population-based study of aging in Tuscany, Italy. Compared with nonanemic persons, urinary hepcidin (nanograms/milligram of urinary creatinine) was significantly lower in iron deficiency and inflammation anemia compared with no anemia or other anemia types. Urinary hepcidin was positively correlated with log(ferritin) and negatively correlated with the soluble transferrin receptor/log(ferritin) ratio but not correlated with markers of inflammation: interleukin-6 (IL-6), IL-1beta, tumor necrosis factor-alpha, and C-reactive protein (CRP). Lower iron was significantly correlated with higher IL-6 and CRP. Adjusting for confounders, IL-6 and CRP remained significantly associated with serum iron, with no evidence that such a relationship was accounted for by variability in urinary hepcidin. In conclusion, elevated proinflammatory markers were associated with anemia and low iron status, but not with higher urinary hepcidin. Future studies should test whether hepcidin production becomes up-regulated only in situations of overt inflammation.